Can Polycystic Ovary Syndrome render middle-aged females vulnerable to severe COVID-19 infection? - Mohsan Ali; Bushra Khalid (Journal of the Pakistan Medical Association, 2022)
Polycystic Ovary Syndrome is the most common endocrine disorder in women around the globe. It is characterized by cysts, usually in ovaries, and caused by excessive androgen production, resulting in menstrual abnormalities, hirsutism, obesity etc. It has a fairly high prevalence in middle-aged Pakistani females¹ as well, and it often (75% of the time) remains undiagnosed.² Besides, PCOS affects the women of age group 18-44 which is often considered low-risk for developing a severe COVID-19 infection, compared to the older people who are more vulnerable.³